Impact biodiesel fuel characteristics on ultra-low emission homogeneous charge compression ignition engine - Rahman, M. M.; Muhamad, Mat Noor; Abdul Adam, Abdullah; Rosli, Abu Bakar; Rizalman, Mamat; Kumaran, Kadirgama; Devarajan, Ramasamy (2018)
Homogeneous charge compression ignition (HCCI) engine has been an active research area due to its potential for high fuel conversion efficiency and extremely low emissions of particulate matter and oxides of nitrogen (NOx). However, the operational range using HCCI combustion in terms of speed and load is restricted because the start of combustion (SOC) and the heat release rate cannot be controlled directly. Depending only on the thermal history and chemical behavior of the cylinder contents, SOC is manipulated by precise manipulation of these variables through methods such as intake temperature and pressure conditioning, fuel blending, variable cylinder geometry, and variable valve timings. In order to design an engine for extended operational range as well as various fuels and blends of fuels, accurate models are needed which are able to model both combustion and performance. The objective of this study is to impact biodiesel fuel characteristics on ultra-low emission homogeneous charge compression ignition engine. In this study, a zero dimensional single-zone numerical simulation with reduced fuel chemistry of various fuels and blends of fuels was developed and validated. It is known for its advantage in reducing computational time compared with a multi-dimensional Computational Fluid Dynamics approach. The main focus of the study is to obtain an improved result for the zero-dimensional model, while the experimental results were used for the purpose of validation. The obtained results show good agreement with the experimental published results and capture important combustion phase trends as engine parameters are varied with a maximum percentage of error which is less than 6% for diesel HCCI and 4% for gasoline HCCI. The combustion phase advances and the combustion duration shorten with the increase of intake charge temperature and the decrease of the engine speed for both diesel and gasoline HCCI. The maximum load successfully increased with increasing the intake pressure. The highest load in this study was 11.27 bar in IMEPg at the condition of 200 kPa in intake air pressure and 333 K in intake air temperature for diesel HCCI and 10.86 bar in IMEPg at the condition of 200 kPa in intake air pressure and 393 K in intake air temperature for gasoline HCCI. It is found that the intake air pressure gives the most sensitive influence on HCCI combustion and performance characteristics. For various fuel blends, thermal efficiency was increased by about 17.71% with Bu30 compared to n-heptane at 393 K intake temperature. IMEP decreased at all intake temperatures with n-heptane. Very low amount of NOx emissions were found with test fuels which is less than 2.5 ppm. NOx emissions were increased with the increase of intake temperature. It is also seen that carbon monoxide (CO) emissions were increased with the increase of alcohol in the test fuels. Maximum CO emissions were found as 0.47% with E30 at 313 K intake temperature. Moreover, higher hydrocarbon (HC) emissions were obtained especially at lower intake temperature when ethanol was used as an additive fuel. Maximum HC emissions were found as 159.6 ppm with E30 test fuel at 313 K intake temperature. As a result, it is found that this numerical investigation can contribute to the determination of proper fuel mixture and intake temperature for the problems such as extending the HCCI operation range, controlling the combustion, preventing knocking combustion and reduction of CO and HC emissions in HCCI combustion. Therefore, future work is recommended to improve the zero-dimensional model by combining it with conditional moment closure model and also experimental test rig develop for the HCCI engine.